2020
DOI: 10.1088/1757-899x/869/4/042004
|View full text |Cite
|
Sign up to set email alerts
|

Geoinformation systems at the selection of engineering infrastructure of pumped storage hydropower for the tuyamuyun complex

Abstract: In this article, we also consider the results of studying the problems and prospects of using information technologies to ensure the introduction of new innovative approaches to analyze engineering infrastructure of future pumped storage hydropower. This study aims to develop a series of advanced Geographic Information System algorithms to locate prospective sites for pumped storage hydropower. It is possible and useful to use the association of outputs from various scientific researches in one GIS-database as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The dynamic effect of the flow on the particle of the bottom soil determines the separation of the particle from the system of surrounding particles and its weighing by the flow. Currently, it is believed that the action of the following forces determines the weighing of particles of bottom soil [19][20][21][22][23][24][25][26][27][28][29][30]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic effect of the flow on the particle of the bottom soil determines the separation of the particle from the system of surrounding particles and its weighing by the flow. Currently, it is believed that the action of the following forces determines the weighing of particles of bottom soil [19][20][21][22][23][24][25][26][27][28][29][30]:…”
Section: Resultsmentioning
confidence: 99%
“…1. Studies carried out at RIWP with the participation of the authors have shown that the obtained ratios make it possible not only to use scientifically grounded methods for calculating the known intake structures of the PS (front chambers, water intakes), but also to analyze the design schemes of dynamic and kinematic flow supply conditions, which allow to establish the nature of the influence of flow parameters and soil particles of bottom and suspended sediments on the process of their layout [18,19]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The method of hydroecological monitoring developed at the Department of Hydropower and Hydraulics is proposed as a virtual stand [18][19][20][21][22][23][24]. Digital mapping and geographic analysis are not entirely new.…”
Section: Hydroecological Monitoring -Virtual Standmentioning
confidence: 99%